Band structure calculation of Ge (1-x-y) Sixsny ternary alloy - Pengpit, Pichitpon; Moontragoon, Pairot; Maensiri, Santi (Asia-Pacific Journal of Science and Technology, 2017)
The code was developed to calculate the energy band structure of Ge(1-x-y)SixSny ternary alloy by using the empirical pseudo potential plan wave method. The Virtual Crystal Approximation (VCA) was adopted to model the alloy. The results show that the direct energy band gap of Ge(1-x-y)SixSny alloy are in the rage of 0-1.3 eV, depending on the amount of Si , Ge and Sn doped. Therefore, the alloy can be used as material for many electronic applications, such as solar cell.